ANALISIS LATIHAN PADA SITUS WWW.CORNELSEN.DE YANG DAPAT MENUNJANG KOMPETENSI DASAR - FLORIDA ALENG, KORNALIA (LATERNE, 2016)
Writing skills in German language is an activity that could produce ideas in a text or a short discourse. As stated in the basic competence point 4.1, 4.2, 4.3 and 4.4 which compose and produce a simple spoken text or written text. For the purpose of learning refers to the basic competence can be achieved, a teacher is required to be able to search or create suitable additional exercises so that the learning objectives can be achieved. There are many different ways that can increase writing skills. One of them is the internet through learning sites. A website of German language learning that can train ability to learn German language is www.cornelsen.de. The problem in this research is which exercises on the site www.cornelsen.de that can support basic competencies point to 4.1, 4.2, and 4.3 for class XI. Based on the problem clearly that the purpose of this research is to find exercises on the site www.cornelsen.de that can support basic competencies points 4.1, 4.2, and 4.3 for class XI. This research is descriptive qualitative. Data sources from this research is www.cornelsen.de and the data is the practice on it. The data was collected by means of literature and then copy and print these practices. Then the practice are categorized based on material learned in class XI. The results showed that the Pluspunkt Deutsch A1 practices in www.cornelsen.de that can be used in German language class XI is lektion 3 which consists of 4 practices, lektion 4 which consists of 3 practices, lektion 6 which consists of 4 practices and lektion 12 which consists of 4 practices. Keywords  :  basic competence, www.cornelsen.de